Social Deixis in The Godfather Movie - Fauzan, Muhammad; Ruminda, Ruminda; Listiani, Toneng (Universitas Pahlawan Tuanku Tambusai, 2025)
This research examined the types and functions of social deixis in The Godfather movie using Levinson’s (1983) theory, focusing on how language reflects power, hierarchy, and social relationships within the mafia world. This research used a qualitative descriptive method. The result of the research identifies 62 occurrences of relational social deixis, consisting of 21 referent honorifics, 33 addressee honorifics, and 8 bystander honorifics, as well as 21 occurrences of absolute social deixis, including 9 authorized speaker instances and 12 authorized recipient instances. The findings reveal that social deixis in The Godfather serves as a linguistic tool to establish authority, reinforce hierarchical structures, and convey respect and familiarity among characters. Through its use of formal address terms, honorifics, and social markers, the movie effectively illustrates how language shapes interpersonal dynamics and power relations, contributing to a deeper understanding of social deixis in cinematic dialogue and its implications in pragmatics.